1996
DOI: 10.1536/ihj.37.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichlormethiazide and Captopril on Nitric Oxide Synthase Activity in the Kidney of Deoxycorticosterone Acetate-salt Hypertensive Rats.

Abstract: SUMMANitric oxide (NO) production is reduced in patients with essential hypertension and in some experimental models. We have investigated the effect of trichiormethiazide and captopril on NO synthase (NOS) activity and glomerular damage in the kidney of deoxycorticosterone acetate (DOCA)-salt hypertensive rats. DOCA-salt rats were induced with weekly injections of DOCA (30mg/kg body weight (BW)) and 1% saline in drinking water after right nephrectomy. As antihypertensive therapies, CAP (captopril, 40mg/kg BW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“… 21,22 Hayakawa et al have shown that administration of L ‐arginine, the NO precursor, improved NO release from an isolated perfused kidney in DOCA‐salt hypertensive rats, suggesting diminished NO synthesis in the kidney. 23 Takanohashi et al 24 have also reported that eNOS expression in renal vessels was decreased by DOCA‐salt treatment, which is consistent with our results. Given these results, we suggest that long‐term volume loading induces glomerular expansion, which, in turn, damages the capillary endothelial cell and decreases eNOS expression, accelerating glomerular injury.…”
Section: Discussionsupporting
confidence: 93%
“… 21,22 Hayakawa et al have shown that administration of L ‐arginine, the NO precursor, improved NO release from an isolated perfused kidney in DOCA‐salt hypertensive rats, suggesting diminished NO synthesis in the kidney. 23 Takanohashi et al 24 have also reported that eNOS expression in renal vessels was decreased by DOCA‐salt treatment, which is consistent with our results. Given these results, we suggest that long‐term volume loading induces glomerular expansion, which, in turn, damages the capillary endothelial cell and decreases eNOS expression, accelerating glomerular injury.…”
Section: Discussionsupporting
confidence: 93%
“…Supporting this, aldosterone infusion in rodents caused hypokalemia and NCC activation, but the correction of hypokalemia by an ENaC inhibitor or potassium supplementation reversed the NCC activation. 114 Moreover, NCC inhibitors ameliorated salt-sensitive hypertension in mineralocorticoidinfused rats 115 and in mice with the kidney-specific deletion of 11b-HSD2; in both cases, NCC is activated via hypokalemia induced by activation of MR-ENaC signals in principal cells. 104 Of note, some studies offer evidence indicating a direct role of aldosterone in NCC regulation, although the modulation of NCC by aldosterone largely depends on change in plasma potassium.…”
Section: Cell Type-specific and Context-dependent Role Of Aldosterone...mentioning
confidence: 99%